A PECS II Block as Post Operative Analgesia After Modified Radical Mastectomy - Rosyadi, Imron -; Anam, Khairul; Mochamat, Mochamat (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2024)
Background: In Indonesia, breast cancer is the most common cancers in 2018, with a mortality rate of 11%. Postoperative pain is a complication that can occur after MRM surgery. The implementation of Enhanced Recovery After Surgery (ERAS) is currently increasingly being applied to breast surgery, one of which is by reducing the use of opioids. Selection of regional anesthetic technique as an alternative used in the form of neuraxial and peripheral nerve blocks. The use of regional anesthetic techniques also reduces the side effects of opioids that are often found, namely Post Operative Nausea and Vomiting (PONV) and pruritus. Analgesic technique with pectoral nerve block (PECS block) is an effective alternative postoperative MRM pain treatment in addition to opioid analgesia.Methods: An analytical experimental study with double-blind randomized controlled trial (RCT) design. The study population was all patients who underwent MRM surgery at Dr. Kariadi General Hospital in May 2021 - August 2021. The study sample consisted of 46 subjects that obtained using the random allocation method, and randomly divided into two groups (PECS II block and control group). Postoperative pain scores, time to first request of rescue analgesic, total dose of rescue analgesic, incidence of PONV, and pruritus within 24 hours postoperative were analyzed in both groups.Results: Based on the results of the analysis, the mean pain scores at 4, 12 and 24 hours postoperative were significantly lower in the PECS II block group compared to the control group (p=0.001, p=0.013, and p=0.003). The mean time to first use of rescue analgesics was longer and the total dose of rescue analgesics was lower in the PECS II block group (p=0.00, p=0.00). The incidence of PONV ((69,5 %) and postoperative pruritus (17,4 %) were more common in the control group (p=0.001, p=0.346)Conclusion: PECS II block is effective as postoperative analgesic after modified radical mastectomy.